Effects of Monoglycerides on Rhodamine 123 Accumulation, Estradiol 17 β-D-Glucuronide Bidirectional Transport and MRP2 Protein Expression within Caco-2 cells - Jia, Jessica X.; Wasan, Kishor M (Journal of Pharmacy & Pharmaceutical Sciences, 2008)
Purpose. Oral drug development had been hindered by the bioavailability issue despite vast market popularity. Lipid excipients had shown to enhance bioavailability of a number of reformulated hydrophobic oral drugs, yet the underlying mechanisms of action by lipids are still unclear. One proposed mechanism is that lipid excipients could facilitate drug uptake by altering the activities of apical membrane intestinal efflux transporters. Thus, this study aimed to investigate the effects of 1-monopalmitin, 1-monoolein and 1-monostearin on the efflux activity and protein expression of multidrug resistance-associated protein 2 (MRP2) in vitro. Methods. The 24-hour non-cytotoxic ranges of these monoglycerides were first determined using MTS and LDH assays in Caco-2 cells. Then, both accumulation and bidirectional transport studies were conducted using 10 uM rhodamine 123 (Rh123) and 10 nM estradiol 17 β-D-glucuronide (E217βG), respectively, to assess the functional activities of MRP2. 50 µM MK-571, a specific MRP1 and MRP2 inhibitor, was used as the positive control in both studies. Western blotting was followed to determine the effect of these monoglycerides on MRP2 protein expression. Results. Caco-2 cells were viable when treated with 1-monopalmitin, 1-monostearin and 1-monoolein at concentrations equal or less than 1000 µM, 1000 µM and 500 µM, respectively. Cells treated with 1-monoplamitin, 1-monostearin, 1-monoolein and MK571 resulted in significant increases in Rh123 accumulation and decreases in E217βG efflux ratio compared to the control (medium treated only). MRP2 protein expressions in 1-monopalmitin and 1-monoolein treated cells were decreased by 19% and 35% compared to the control; however, there was no change of MRP2 protein expression in 1-monostearin treated cells. Conclusions. These findings suggested that 1-monoolein, 1-monostearin and 1-monopalmitin could attenuate the activity of MRP2 and possibly other efflux transporters in Caco-2 cells. The reduction of efflux activity of MRP2 by 1-monoolein treatment could be partially accounted by the non-specific down-regulation of MRP2 protein expression.